Sintering Behaviour of ZnO:Cu Ceramics Fabricated by Sol-Gel Derived Powders - Özer, Mehmet; Bahşi Oral, Zehra Banu; Oral, Ahmet Yavuz; Aslan, Muhammed Hasan; Kayahan, Ersin (Polish Acad Sciences inst Physics, Al Lotnikow 32-46, Pl-02-668 Warsaw, Poland, 2012)
Doped zinc(II) oxide (ZnO:Cu) ceramics were prepared from sol gel derived nanocrystalline powders. Powders were prepared by dissolving zinc and copper acetates in isopropyl alcohol. Ethanolamine was used to enhance the solubility of acetates. Powders were produced by the calcination of the dried gels at 750 degrees C. The crystal size of the undoped powders were uniform and around 50 nm while grain size of Cu doped powders varied between 0.3 and 2 mu m. X-ray mapping of the powders showed that Cu was not homogeneously distributed and some particles had higher Cu content. After pressing of the powders, both doped and undoped ceramics were sintered at 1200 degrees C for 2 h. Microstructure of the Cu doped ceramics showed that Cu atoms partially dissolved in ZnO matrix and the rest formed a second phase in the grain boundaries. Average grain size of the ZnO:Cu ceramics was around 30 mu m. Relative densities of the ceramics increased from 0.695 to 0.857 by Cu doping.
Keywords: electrical-properties; doped zno; varistors; films; elektrik özellikleri; varistörler; filmler